Reações adversas causadas por antimicrobianos em pacientes pediátricos de um hospital público de Fortaleza-CE - Alexandre Júnior, Ronaldo Gomes (2019)
In pediatrics, there is not always the best scientific evidence to support drug therapy, contributing to the occurrence of adverse events. These events include adverse drug reactions (ADRs), which are considered a worldwide public health problem. Particularly, antimicrobial drugs are among the most implicated in the occurrence of ADR. In this context, this study aimed to study the adverse reactions caused by antimicrobials in pediatric patients in a public hospital in northeastern Brazil, analyzing ADRs as to causality, avoidability and seriousness. For this purpose, intensive monitoring of pediatric patients was performed through the analysis of medical records (n = 314), from December 2018 to May 2019, in order to identify cases of suspected ADR caused by antimicrobial drugs (ADR-ATM). Causality of ADRs were determined using the Naranjo algorithm and the Liverpool Causality Assessment Tool, avoidability using the Liverpool Avoidability Assessment Tool and gravity using the adapted Hartwig scale. Reactions were categorized using the Adverse Reaction Terminology - World Health Organization. For data analysis, IBM SPSS Statistics and descriptive statistics were used. In the comparisons, a significance level was used when p <0.05. The incidence of suspected ADR-ATM was 14.65% (n = 46). Most of the children who had ADR-ATM were between 0 and 1 year old (38.46%; n = 15), used between 3 and 4 medications (41.03%; n = 16), with an average of 25,94 days of hospitalization. The main antimicrobial agents involved in the suspicions were ceftriaxone (36.17%) and oxacillin (23.41%). The predominant suspicions of ADR-ATM were those related to disorders of the gastrointestinal system (50,91%) and skin and related disorders (29,09%). The number of medications in use (p <0.0001) and the number of days of hospitalization (p = 0.004) were shown to be risk factors for the occurrence of ADR-ATM. The findings showed that most antimicrobials are probably (89.13%) implicated in the suspected adverse reactions identified, especially ceftriaxone, and that almost half of these reactions (45,65%) could possibly be avoided if the necessary strategies had been taken. Thus, the prevention of adverse reactions could prevent damage to the health of patients, even favoring the minimization of expenses for the health system.